2015
DOI: 10.17305/bjbms.2015.552
|View full text |Cite
|
Sign up to set email alerts
|

The importance of speckle tracking echocardiography in the early detection of left ventricular dysfunction in patients with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is characterized by hormonal and metabolic abnormalities and is thought to increase a risk for cardiovascular diseases. In this study we use speckle tracking echocardiography (STE) to evaluate left ventricular (LV) dysfunction in the early period of the disease. We enrolled 31 patients with PCOS and 32 healthy volunteers as a control group. The participants' ages ranged between 18 and 40 years. PCOS was diagnosed according to the Rotterdam criteria. LV strain (LS) and strain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Similar findings were reported by Demirelli et al. showing reduced LV GLS in PCOS patients 39 . In current study, we have showed that LVGLS was diminished in PSW‐positive PCOS patients and was correlated with PSW velocity.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported by Demirelli et al. showing reduced LV GLS in PCOS patients 39 . In current study, we have showed that LVGLS was diminished in PSW‐positive PCOS patients and was correlated with PSW velocity.…”
Section: Discussionsupporting
confidence: 92%